1989
DOI: 10.1111/j.1432-1033.1989.tb14861.x
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear‐coded chloroplast 22‐kDa heat‐shock protein of Chlamydomonas

Abstract: A cDNA clone, pCHS62, was isolated using poly(A)-rich RNA from heat-shocked Chlumydomonus reinhurdtii cells. The clone has a length of 1.1 kb and codes for the complete heat-shock protein which was reported to be associated with the grana region of the thylakoid membranes and ascribes protection against photoinhibition during heat-shock. An expression vector prepared in the pUC19 plasmid was used to obtain a fusion protein against which rabbit polyclonal antibodies have been raised. The antibodies react specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…Like many other heat shock proteins, members of the alpha-crystallin family can be found in a variety of eukaryotes, i.e., in plant cells (18,32,36), various animal and insect cells (humans, hsp27; Drosophila sp., hsp26; spiny dogfish, alpha-crystallin) (11,22,24), and in yeast cells (hsp26) (5). However, in contrast to the 70K (DnaK and hsp70) and 60K (GroEL and hsp60) families, members of the alpha-crystallin family have not been reported as major proteins in prokaryotes (50).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like many other heat shock proteins, members of the alpha-crystallin family can be found in a variety of eukaryotes, i.e., in plant cells (18,32,36), various animal and insect cells (humans, hsp27; Drosophila sp., hsp26; spiny dogfish, alpha-crystallin) (11,22,24), and in yeast cells (hsp26) (5). However, in contrast to the 70K (DnaK and hsp70) and 60K (GroEL and hsp60) families, members of the alpha-crystallin family have not been reported as major proteins in prokaryotes (50).…”
Section: Methodsmentioning
confidence: 99%
“…A common feature of the low-molecular-weight heat shock proteins is a well-conserved short sequence near the C terminus with a derived consensus sequence, D/N-G-V-L-T-IIV-X-V/A (18), corresponding to a sequence in the alphacrystallin protein. Both the 14K protein of M. tuberculosis and the 18K protein of M. leprae contain this region, i.e., KGILTVSV, aa 118-125, and EGVLKLSI, aa 108-115, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In C reinhardtii, preferential association of this protein with the thylakoid membranes was suggested to be with the grana stacks (8,12,34). This was corroborated by immunocytochemical localization of most of the 22-kD HSP in the granal fraction of thylakoid membranes isolated from heated cells (8).…”
Section: Vierling (Personal Communication)mentioning
confidence: 69%
“…2). Confirmation of the transcriptional origin of the HSP22 homolog of pea, soybean, maize, and C reinhardtii was obtained by the isolation of specific cDNA clones for each protein (8,23,40). However, only one study so far has reported chloroplast-encoded HSPs in higher plants (14), although no genes for such HSPs have yet been isolated.…”
Section: Vierling (Personal Communication)mentioning
confidence: 99%